SUCCESSFUL MANAGEMENT OF PENETRATING KERATOPLASTY IN PEDIATRIC PATIENTS WITH CORNEAL TRAUMA - Wardani, Made Kusuma; Siska, Siska; Kusumadjaja, I Made Agus (JURNAL WIDYA MEDIKA, 2024)
Introduction: Corneal perforation is an ophthalmic emergency and requires immediate medical and surgical treatment. The most common causes of corneal perforation are infection, inflammation, or trauma. Case Report: A 9-year-old boy came with complaints pain in his right eye for 2 days of BATH, he had history of hit by a sharp tip wire. Visual acuity on the right eye was 6/60 PH 6/30, revealed ciliary injection, corneal rupture with the avulsion, size 6x3x1mm, stromal oedema, iris prolapse, shallow anterior chamber, eye pressure was n-1/p. Patient was diagnosed with corneal rupture and iris prolapse. Patient was treated by penetrating keratoplasty. The last condition of the graft is quite good and the visual acuity was 6/15. Discussion: Perforation cause by the traumatic more than 3 mm can be treated by the penetrating keratoplasty as an emergency situation. Tissue adhesives, such as cyanoacrylate glue, amniotic membrane multilayer transplantation, conjunctival flap, or patch graft, can be used to treat small corneal defects. The success of keratoplasty is measured by corneal clarity and functional refractive outcomes. Conclusion: The success rate of emergency keratoplasty in corneal perforations reported by various studies and one of these case reports reinforces the importance of eye banking in corneal graft supplies.